2007
DOI: 10.1021/np070211i
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Compounds fromCordia fragrantissima Collected in Burma (Myanmar)

Abstract: A methanol extract of the wood of Cordia fragrantissima, collected in Burma (Myanmar), was found to exhibit significant activity against Leishmania major. Bioassay-guided fractionation of this extract using several chromatographic techniques afforded three new compounds (1-3) and five known compounds (4-8). The structures of the new compounds were revealed on the basis of spectroscopic data interpretation and by X-ray crystallographic analysis. Interestingly, the new compounds, despite the presence of asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…[58,59] Later, six new hydroquinones, namely alliodorol (2), allioquinol C (3), cordiachromen A (4), cordallinol (9), Cordiaquinol C (11) and cordiol A (10), were reported to be found in the acetone extract of heartwood of C. alliodora. [60] Ioset et al [61] isolated 2-(2Z)-(3-hydroxy-3,7-dimethylocta-2,6-dienyl)-1,4-benzenediol (16) from the root bark.…”
Section: Hydroquinonementioning
confidence: 99%
See 1 more Smart Citation
“…[58,59] Later, six new hydroquinones, namely alliodorol (2), allioquinol C (3), cordiachromen A (4), cordallinol (9), Cordiaquinol C (11) and cordiol A (10), were reported to be found in the acetone extract of heartwood of C. alliodora. [60] Ioset et al [61] isolated 2-(2Z)-(3-hydroxy-3,7-dimethylocta-2,6-dienyl)-1,4-benzenediol (16) from the root bark.…”
Section: Hydroquinonementioning
confidence: 99%
“…As per structural characteristics, they are classified into four classes: (1) oleanane type isolated from C. alliodora, C. cylindrostachya, C. piauhiensis, C. latifolia and C. multispicata [74][75][76][77][78] ; (2) lupane type identified from C. obliqua and C. gilletii [79][80][81] ; (3) ursane type reported from C. retusa, C. obliqua, C. rothii and C. multispicata [80,[82][83][84][85] ; and (4) dammarane type found in C. spinescens, C. multispicata and C. verbenacea. [86][87][88] [58] C. fragrantissima [59] Heartwood Timber Alliodorol (2) C. alliodora [58] Heartwood Allioquinol C (3) C. alliodora [58] Heartwood Cordiachrome A (4) C. alliodora [58] Heartwood Cordiachrome A (5) C. fragrantissima [59] Timber Cordiachrome B (6) C. fragrantissima [59] Timber Cordiachrome C (7)…”
Section: Triterpenoidsmentioning
confidence: 99%
“…[5][6][7][8][9][10] These quinoid compounds, known as cordiaquinones, could be considered as chemotaxinomical markers for the Cordia genus. Nevertheless, the occurrence in their producing plants is limited to the roots and rarely to the trunk wood.…”
Section: Introductionmentioning
confidence: 99%
“…We have already reported several leishmanicidal constituents of medicinal plants in tropical and subtropical regions (Peru, Myanmar, Bolivia, Pakistan, etc.). [7][8][9][10][11] In the first screening of hundreds of Peruvian medicinal plant extracts for leishmanicidal activity, we found that the extract of Bocconia pearcei fruit exhibited potent activity.…”
mentioning
confidence: 99%